Пчеловодчество Украины: проблемы и перспективы отрасли и экспорта - Горбунов, Николай Петрович; Драган, М. В. (НТУ "ХПІ", 2017)
В статье рассмотрено современное состояние и проблемы развития рынка и экспорта продукции пчеловодства. Установлено деструктивное влияние факторов микро и макросреды, на отечественное пчеловодство и их влияние на экспортоориентированную направленность отрасли. Очерчены главные направления решения проблемы.

The article considers the current state and problems of market development and export of bee products. The destructive influence of micro and macroenvironment factors, on domestic beekeeping and their influence on the export-oriented direction of the industry has been established. The main directions of the solution of the problem are out lined.
Beekeeping of Ukraine: problems and prospects of the industry and exports
Keywords: продукция пчеловодства; украинский мед; медовая отрасль; мировой рынок меда; европейский оптовый покупатель; beekeeping products; Ukrainian honey; honey export; beekeeping; honey industry